Comparative Genetic Characterization of Prolactin Gene between Giriraja and Indigenous Chicken - Singh, Ajeet; Kumar S, Naveen; H M, Yathish; Inamdar, Basavraj; V, Malathi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to determine the polymorphism and to explore the possible SNPs in prolactin gene among the Giriraja and Indigenous chicken using PCR-RFLP. About 80 birds each of Giriraja and Indigenous chicken were genotyped for promoter regions 1 and 2 (C-2402T and C- 2161G) of prolactin gene by employing published primers. The restriction enzymes, AluI and Csp6I were utilized for genotyping polymorphisms of C-2402T and C-2161G, respectively. At promoter region 1 (24 bp indel at -358) of prolactin gene, the proportions of DD and ID genotypes were higher in Giriraja (0.45) and Indigenous (0.44) chicken. However, the frequency of D allele (0.775 and 0.631) was higher in both the studied populations. Whereas, for promoter region 2 of prolactin gene, the frequencies of T allele (C-2402T) and G allele (C-2161G) were higher in Giriraja (0.806 and 0.694) and Indigenous (0.644 and 0.525) confirming that T alleles are predominant in native or indigenous chicken. Further, three SNPs, viz., C>T transition at 161 bp, T>C transition at 371 bp and C>G transversion at 402 bp were detected at promoter region 2 (C-2402T and C-2161G) in T/G allele compared to C allele.